Statin Therapy to Revert Hypercoagulability and Prevent Venous Thromboembolism: A Narrative Review - Orsi, Fernanda A.; Cannegieter, Suzanne C.; Lijfering, Willem M. (Seminars in Thrombosis and Hemostasis, 2019)
Venous thromboembolism (VTE) causes a major disease burden worldwide, so that effective preventive measures are warranted. Although oral anticoagulation is effective in preventing VTE episodes, bleeding complications are a major concern that may lead to treatment avoidance. Statin therapy, which is widely used for prevention of arterial cardiovascular disease, is a promising alternative treatment for VTE prophylaxis, as the drug may affect hemostasis without increasing the risk of bleeding. In the past years, clinical studies have suggested that statins can interfere with blood coagulation and, in turn, reduce the risk of VTE. These effects, however, are still regarded with skepticism, as the underlying mechanisms by which statins may affect hemostasis in humans are not clear and data showing that statin therapy reduces VTE risk mostly came from observational studies, while only one randomized trial was conducted to evaluate this issue. In this review, the authors summarize the currently available evidence regarding the effect of statin therapy on coagulation and on VTE prevention. Recent randomized data showed that statin therapy, in particular rosuvastatin, leads to decreased levels of coagulation factors in patients with prior VTE. This evidence provides a reasonable basis for interventional studies necessary to establish the efficacy of statins on reducing the risk of incident and recurrent VTE.
Keywords: blood coagulation; clinical trials; hydroxymethylglutaryl-CoA reductase inhibitors; prevention; venous thrombosis